Nanoestruturas formadas por redes orgânicas covalentes - Maurisan Alves Lino (2007)
In this work we apply first-principles calculations based on the Density Functional Theory (DFT) to investigate structural and electronic properties of covalent organic frameworks (COF's). These structures were recently obtained experimentally and constitute a new class of porous nanostructures composed only of light elements (H, C, B and O atoms).The covalent framework de¯nes a graphitic-type structure with pore sizes in the range 15-30 ºA. We show that the gap energies of these materials depend on the building block molecules that form the framework. Also, we investigate the energetic stability of nanotubes and fullerenes based on these compounds. The nanotubes are obtained by rolling up COF sheets, and their stability is determined by comparison of their strainenergy with nanotubes based on other materials, such as carbon, GaS and GaSe, and with surface energies of COF ribbons. Moreover, we show that a fullerene based on COF, with a diameter around 40ºA, may also be stable. We employ the SIESTA implementation of the DFT formalism, which makes use of pseudopotentials and a basis set composed of pseudo atomic orbitals of ¯nite range.